ENGLISH REMOVAL FOR ELEMENTARY SCHOOL IN 2013 CURRICULUM; A CARELESS OR CAREFUL STEP? - Yulian Purnama (University of Muhammadiyah Purwokerto, 2014)
The idea of removing English for elementary school in 2013 curriculum has shocked the Indonesian education practitioners. So far, English has been considered as a favorite and prestigious subject for some modern elementary schools. English lessons is claimed to be important and is still needed by the young learn-ers. Given the context of EFL (English as a Foreign Language) teaching English in Indonesia, of course, may not equate with the teaching of English in Singapore where English is in the context of ESL (English as a Second Language). As the right method and strategy may be given to the learners, the development of lan-guage skills for children aged 6-12 years-old will not be disturbed. Then if the mother tongue, that is Bahasa Indonesia, would not be a mess if at the same time the students need to learn a foreign language. In the end, learning English will not lose identity or sense of nationalism of the students. Keywords: Young learners, English, 2013 Curriculum